Pengembangan Media Pembelajaran Berbasis Android Aplikasi RIMath untuk Mendukung Literasi Digital - Ulum, Achmad Miftachul; Khumainah, Nanda Dila Zahrotul; Nursirot, M. Arul Sholehuddin (Pusat Studi Pengembangan Pembelajaran Matematika Sekolah UIN Sunan Kalijaga Yogyakarta Jl. Marsda Adisucipto, Yogyakarta 55281, 2024)
Education is very essential for the progress of a country. This is because education can provide enormous benefits to the younger generation. In carrying out education, learning media is needed to convey material and information by teachers to students. Media is very important in learning. So teachers must look for efficient media to apply in learning so that students are happy, comfortable and enthusiastic in learning. The approach used in this research is R&D with a 4D model. There are four stages that will be carried out in this research, namely Define, Design, Develop, and Disseminate. In processing the data, researchers used descriptive analysis techniques to draw conclusions from the data obtained. In the initial stage, researchers define the problems that exist in mathematics learning. The next stage is that researchers design learning media according to teacher needs to support digital literacy. In the third stage, the researchers carried out validation. As for the validation percentage results, the material aspect received 78.125%, including the very feasible category, the integration aspect received 91.6%, including the very feasible category, and the media aspect received 68.75%, including the appropriate category. The final stage is disseminate, researchers disseminate learning media to MTS Miftahul Ulum.